Intelligent electric power networks (Smart Grids) (Research, Society and Development, 2021)
In the country and in the world, the Intelligent Electricity Grid is currently in a stage of embryonic growth, similar to the internet in the early 1980s, still having many possibilities for consumers, companies, energy concessionaires, governments, suppliers technology and the development of new capabilities in the so-called “sustainable economy”. There are still some doubts and uncertainties about the regulation for the establishment of adequate legislation for the commercialization of electric energy in order to allow the adequate use of dynamic pricing and of microgeneration energy. The purpose of this article is to discuss and expose about Intelligent Electric Networks or Smart Grid, in English, its concept, purpose, components. Also about regulation, what must be changed to adapt to these new technologies and their modern measurements. The research method used was descriptive, where data collection techniques were used through searches in recognized bibliographies and articles, in order to elucidate and better illustrate the Intelligent Electric Network. Finally, it is concluded how the massification of this technology in Brazil should be done in order to be agile and efficient.